Recombination of Poliovirus RNA Proceeds in Mixed Replication Complexes Originating from Distinct Replication Start Sites - Egger, Denise (American Society for Microbiology, 2002)
Genetic recombination occurs frequently during replication of picornaviruses. To explore the intracellular site and structures involved in recombination, HeLa cells were infected with poliovirus type 1 Mahoney and type 2 Sabin. The two genomes were located by fluorescent in situ hybridization and confocal microscopy. For hybridization, type-specific fluorescent riboprobes were used to visualize the same genomic region where, in parallel, recombination was demonstrated with type-specific reverse transcription-PCR and sequencing. The hybridization analysis indicated that >85% of the replication complexes contained both type 1 and type 2 RNA sequences aligned at a lateral distance of 50 nm or less. Sequential infection of cells ruled out the possibility that the high percentage of mixed replication complexes was due to aggregation of input virus. Visualization of input genomic RNA over time showed that the viral genomes migrated to relatively few distinct, and thus presumably specific, perinuclear sites where replication started. The first recombinant RNA strands could be detected concomitantly with the onset of RNA replication. The limited number of start sites for replication may be the reason for the observed preferential formation of mixed replication complexes, each accommodating several parental RNA strands and thus allowing recombination.